The required teaching skills for mathematics teachers to support students with special learning difficulties in elementary schools from the perspective of education specialists - Alsharif, Hassan Mohammed (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the skills needed for primary school mathematicians in light of the needs of students with learning problems in Hedgehog Province, and the study followed the descriptive survey curriculum, and the tool consisted of a questionnaire applied to a sample of (183) primary school teachers. The results showed that teachers needed skills (teaching methods and methods, treatment of cognitive and attention problems) to a high degree, while skills (use of teaching methods and activities) emerged to a moderate degree. The results also showed differences due to gender differences in favour of teachers, differences in favour of graduate graduates, and differences in favour of experienced people under 10 years of age. There were also differences due to the different number of courses in therapeutic teaching, in favour of those who did not receive any courses.